Odontogenic onset mucormycosis in a post-COVID-19 diabetic patient: an unusual report - Bahia, Marcelo Santos; Medeiros, Yuri de Lima; Mota, Maria Emília; Kadooka, Marcella Yumi; Vargas, Pablo Agustin; Sverzut, Cassio Edvard; Trivellato, Alexandre Elias (Journal of Oral Diagnosis, 2024)
Fungal infections associated with COVID-19 have been responsible for exacerbating the course of the disease, with mucormycosis being one of the main reported conditions. Although dental involvement is commonly considered an extension of rhinocerebral disease, some authors recognize it as a distinct clinical entity characterized by odontogenic onset mucormycosis. The aim of this study was to report the diagnosis of mucormycosis following drainage of odontogenic abscess in a post-COVID-19 diabetic patient. A 69-year-old post-COVID-19 diabetic man sought a maxillofacial surgery service due to complaints of pain and swelling on the right side of the face. Edema, dental mobility, and purulent discharge associated with teeth 16 and 17 were noted. Drainage of the odontogenic abscess was performed, and cone-beam computed tomography was requested. Tomographic findings included a suggestive image of osteolytic lesion in the posterior region of the maxilla extending into the right maxillary sinus. Extraction of teeth 16 and 17 and biopsy of areas of necrotic bone were performed. Histopathological aspects favored the diagnosis of mucormycosis. The patient was referred for treatment with Amphotericin B. The diagnosis of mucormycosis should be considered in immunosuppressed patients, especially those with diabetes mellitus and post-COVID-19, presenting signs and symptoms of odontogenic infection.